2008
DOI: 10.1354/vp.45-5-640
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Circovirus 2 Inclusion Bodies in Pulmonary and Renal Epithelial Cells

Abstract: Porcine circovirus 2 (PCV2) is the cause of postweaning multisystemic wasting syndrome (PMWS). The most common lesions of PMWS are lymphohistiocytic to granulomatous lymphadenitis, interstitial pneumonia and interstitial nephritis, with intracytoplasmic amphophilic botryoid inclusion bodies in macrophages. In addition to these typical changes, intracytoplasmic botryoid inclusion bodies were observed in bronchial, bronchial glandular, and renal tubular epithelium of several pigs from 4 different farms in Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…At present, some works about PCV-2 inclusion bodies in lymph nodes, lungs and kidneys in PMWS have been achieved in a few studies Huang et al 2008). These studies have shown the intracytoplasmic inclusions in macrophages in lymphoid organs, bronchial glandular and renal tubular epithelial cells of PCV-2 infected pig.…”
Section: Discussionmentioning
confidence: 99%
“…At present, some works about PCV-2 inclusion bodies in lymph nodes, lungs and kidneys in PMWS have been achieved in a few studies Huang et al 2008). These studies have shown the intracytoplasmic inclusions in macrophages in lymphoid organs, bronchial glandular and renal tubular epithelial cells of PCV-2 infected pig.…”
Section: Discussionmentioning
confidence: 99%
“…44 Intracytoplasmic botryoid inclusion bodies can rarely be observed in the renal tubular epithelium in pigs with systemic PCVAD. 38 Renal tubular epithelial necrosis with extensive interstitial edema and hemorrhage; lymphoplasmacytic, eosinophilic, and histiocytic tubulointerstitial nephritis; and numerous botryoid intracytoplasmic inclusions within the renal tubular epithelium and interstitial macrophages were identified in a pig with acute renal failure. These lesions were associated with PCV2 antigen by IHC and PCV2 virus particles by electron microscopy indicating a causative relationship.…”
Section: Urinary Systemmentioning
confidence: 94%
“…23 Recently, it was reported that intracytoplasmic botryoid inclusion bodies that displayed PCV2-specific staining were observed in bronchial and bronchial glandular epithelial cells. 38 Mild nonsuppurative interstitial pneumonia 51,82,88 or broncho-pneumonia, 10,123 perhaps due to concurrent bacterial infection, have been reported in fetuses and newborn piglets infected with PCV2 in utero. PCV2 antigen was also associated with intraluminal polyps in bronchiolitis obliterans organizing pneumonia.…”
Section: Respiratory Systemmentioning
confidence: 99%
“…Meanwhile, the presence of typical granulomatous lesions with multinuclear giant cells was also recorded in the lymphatic tissue (Becskei et al, 2010). PCV2 inclusion bodies were demonstrated to be located in the cytoplasm of epithelial cells by immunohistochemical staining for PCV2 and cytokeratin antigens and by ultrastructural demonstration of viral particles in the inclusion bodies within renal tubular epithelium (Huang et al, 2008).…”
mentioning
confidence: 91%